Inversiones en Los intereses creados, de Jacinto Benavente. - Popovic Karic, Pol (Neophilologus, 2019)
In this paper, the comedy Los intereses creados by Jacinto Benavente will be analyzed from two points of view: inversions and investments. On one hand, I will analyze the substitution or the inversion of dramatic and thematic concepts; and on the other, I will focus on the financial investments. The theoretical approaches to irony by Plato, Booth and Peter Roster will be used to analyze substitutions and investments. The complementary parts—substitutions, investments, irony and the characters—place this play in the rich tradition of the comedy and, even more specifically, in the context of commedia dell'arte.